Associations between body mass index and the risk of mortality from lung cancer: A dose–response PRISMA-compliant meta-analysis of prospective cohort studies. Issue 34 (August 2017) - Shen, Ning; Fu, Ping; Cui, Bin; Bu, Chun-Ying; Bi, Jing-Wang
Abstract: Background: Whether body mass index (BMI) is associated with the risk of mortality from lung cancer (LC) is controversial, and the shape of dose–response relationship on this topic is not well-established. Thus, a dose–response meta-analysis was performed to clarify this association. Methods: A search of PubMed and EMBASE was conducted, and 2-stage random-effect dose–response model was used to yield summary relative risks and its shape. Results: Fifteen prospective cohort studies were eligible for inclusion criteria. The combined relative risks per 5 kg/m 2 in BMI for risk of LC mortality is 0.94 (95% confidence interval] 0.92–0.96), and nonlinear association was found ( P nonlinearity  < .0001), which indicated that compared with higher BMI, lower BMI showed higher LC mortality risk. Subgroup analyses revealed that this obesity paradox remained regardless of number of cases, follow-up duration, and study location, but this relationship was not observed among nonsmokers. Conclusion: A nonlinear association between BMI and the risk of LC mortality was found, and higher BMI participants have a lower risk of LC death than slim people. Abstract : Supplemental Digital Content is available in the text